Scientific Truth and Judicial Truth: Philosophy and Method - Mancini, Massimo (Frontiers in Law, 2023)
A sinthetic excursus of modern epistemology across some methodological contributes of Aristotle, Descartes, Galilei and Freud, with special regard to alethic and verisimilar knowledge in law sciences and legal reasoning, in order to analyse dialectic opposition of involved parts in legal argumentations and verdict’s rational motivation in trials.